Dukungan Psikologis Keluarga Berpengaruh Dominan terhadap Tipe Demensia pada Lansia - Ros Endah Happy Patriyani; Junaiti Sahar; Dewi Gayatri; Raden Siti Maryam (Jurnal Ilmu dan Teknologi Kesehatan, 2019)
This study purposes to know the difference of elder’s characteristics and family support to types of dementia for elderly. Study’s design was analytic correlation that applied cross sectional approach. Sampling technique was simple random sampling with multistage random sampling. There were 109 elderly with dementia in the age of 60 years old or more. Types of dementia was measured by Mini Mental State Examination. T test independent was used as statistical test. A multiple regression linier used to get elderly ‘s characteristics that influence dominantly types of dementia. There were the elder’s age (p=0,000) and the elder’s educational background (p=0,000). Based on the type of support, this study found significant differences on phsycological support (p=0,011), appraisal support (p=0,013), instrumental support (p=0,030). Type of family’s support that dominantly influence type of dementia was phsycological support. It can be cloncluded that phsycological support can increase elder’s spirit and motivation to have healthy life. This study recommended that to prevent dementia become worse needs nursing care that includes promotion and prevention such as early detection, health education about dementia, and family still consistently provides support to elderly.